2009
DOI: 10.1038/sj.bjc.6605483
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of angiogenesis and their role in the development of VEGF inhibitors

Abstract: Vascular endothelial growth factor (VEGF) has been confirmed as an important therapeutic target in randomised clinical trials in multiple disease settings. However, the extent to which individual patients benefit from VEGF inhibitors is unclear. If we are to optimise the use of these drugs or develop combination regimens that build on this efficacy, it is critical to identify those patients who are likely to benefit, particularly as these agents can be toxic and are expensive. To this end, biomarkers have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(163 citation statements)
references
References 98 publications
8
153
0
2
Order By: Relevance
“…Consistent with prior reports by our group and others evaluating anti-VEGF monotherapy, in this study MMP-2, PlGF, VCAM-1, and VEGF-D were increased, while Ang-2, MMP-9, and s-VEGFR2 were decreased in response to the combination of bevacizumab and everolimus. The magnitudes of these changes appear to be broadly consistent with those previously described for bevacizumab monotherapy (18,22), suggesting these changes were driven primarily by VEGF but not mTOR inhibition.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with prior reports by our group and others evaluating anti-VEGF monotherapy, in this study MMP-2, PlGF, VCAM-1, and VEGF-D were increased, while Ang-2, MMP-9, and s-VEGFR2 were decreased in response to the combination of bevacizumab and everolimus. The magnitudes of these changes appear to be broadly consistent with those previously described for bevacizumab monotherapy (18,22), suggesting these changes were driven primarily by VEGF but not mTOR inhibition.…”
Section: Discussionsupporting
confidence: 73%
“…Conversely, oral VEGFR-2 inhibitors reduce circulating levels of the receptor, accompanied by increased VEGF production (49, 50, reviewed in ref. 51) as a compensatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to sVEGFR-1, sVEGFR-2 is unable to carry out tyrosine transphosphorylation and activate the downstream signal transduction of angiogenesis, due to the lack of the tyrosine kinase domain (20). The activation of VEGFR-2 reportedly plays a significant role in tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A study recently showed that hepatocyte growth factor (HGF) may be a surrogate marker for the clinical benefit of sorafenib (20). In addition to HGF, various molecules have been considered as useful biological markers for anti-angiogenic therapy, such as circulating endothelial progenitor cells and the soluble form of VEGF receptors (20).…”
Section: Introductionmentioning
confidence: 99%